ANALISIS FUNGSI TINDAK TUTUR EKSPRESIF PADA “FILM SATU KAKAK 7 KEPONAKAN KARYA ARSWENDO ATMOWILOTO” - Eka Kurniati Eka Kurniati; Khermarinah; Welti Wediati (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2026)
This study aims to analyze the role of expressive speech acts in the film Satu Kakak Tujuh Keponakan. Expressive speech acts are utterances used by speakers to convey or demonstrate psychological states, emotions, and attitudes regarding a specific situation or event. This study employs a descriptive qualitative method. The research data consist of dialogues between characters in the film Satu Kakak Tujuh Keponakan, specifically utterances containing expressive speech acts. Data collection was carried out using the